Editorial - Soares, Márlon Hebert Flora Barbosa; Mesquita, Nyuara Araújo da Silva; Cavalcanti, Eduardo Luiz Dias (Revista Debates em Ensino de Química, 2017)
Editorial da REDEQUIM, volume 2, número 2 (especial) - JALEQUIM Level 2